2020
DOI: 10.1002/csc2.20095
|View full text |Cite
|
Sign up to set email alerts
|

The fungal endophyte Epichloë festucae var. lolii plays a limited role in mediating crown rust severity in perennial ryegrass

Abstract: Perennial ryegrass (Lolium perenne L.) is an important turf and forage species that often becomes infected with Puccinia coronata f. sp. lolii, the causal pathogen of crown rust. Disease control through clavicipitaceous endophytes has been proposed as a potential biocontrol. Two field experiments were designed to determine the influence of native Epichloë endophyte infection on natural rust development across a diverse panel of perennial ryegrass germplasm. Experiment 1 used an isogenic population design in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…At each site, digital images (size 4,000 × 3,000 pixels) were collected with a lighted camera box, described by Heineck et al. (2020), every 7 or 14 d until 70 to 90 d after planting (DAP), and after winter on 1 May (∼8 mo after planting [MAP]), and 1 June (∼9 MAP) and analyzed with ImageJ (hue: 47–150; saturation: 0–255; brightness: 10–255) (v.1.52a; Schneider et al., 2012) to assess green vegetation cover (0‐100%). Using the methods of Braun et al.…”
Section: Methodsmentioning
confidence: 99%
“…At each site, digital images (size 4,000 × 3,000 pixels) were collected with a lighted camera box, described by Heineck et al. (2020), every 7 or 14 d until 70 to 90 d after planting (DAP), and after winter on 1 May (∼8 mo after planting [MAP]), and 1 June (∼9 MAP) and analyzed with ImageJ (hue: 47–150; saturation: 0–255; brightness: 10–255) (v.1.52a; Schneider et al., 2012) to assess green vegetation cover (0‐100%). Using the methods of Braun et al.…”
Section: Methodsmentioning
confidence: 99%
“…Epichloë-grass associations are known to benefit grasses in a number of ways, including increased growth (Gundel et al, 2013), better tolerance to water deficits (Rho et al, 2018) and resistance to pathogens (Xia et al, 2018) and herbivores (Bastias et al, 2017), the latter mainly via production of endophyte specific protective alkaloids (nitrogenous compounds) (Bastias et al, 2017). While some studies suggest endophytes play a limited role in stress alleviation (Niones and Takemoto, 2014;Wiewióra et al, 2015;Heineck et al, 2020), and might have antagonistic responses under extreme resource limitations conditions (Cheplick et al, 1989;Cheplick, 2007;Saikkonen et al, 2016), it is recognized that their beneficial effects are now widely reported (Kuldau and Bacon, 2008;Perez et al, 2017). Because of these benefits, animal-safe endophytes strains (e.g., AR1, AR31, AR584), that don't have the genes accountable for producing mammalian toxic alkaloids, are commercially available in marketed varieties of several perennial forage grasses such as tall fescue, perennial ryegrass, and cocksfoot (Gundel et al, 2013;Kauppinen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the most common genera are known plant pathogens ( Limonomyces , Parastagonospora ), and some pathogens known to be associated with tall fescue and related grasses were also found in our dataset, e.g., Puccinia spp. (rust) [ 52 , 53 ] and Fusarium oxysporum [ 54 ]. Based on the FungalTraits database [ 50 ], other common fungal guilds in our dataset include animal pathogens, endophytes, wood saprotrophs, and lichen parasites.…”
Section: Discussionmentioning
confidence: 99%